THE OPPORTUNITIES FOR VIRTUAL TOURISM DURING SOCIAL DISTANCING - Sirisungsuchol, Naruemon (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The aimed of this study is to find out whether virtual tourism would have a chance to become more well-known and able to help booting tourism business during social distancing. Researcher used qualitative method to collect and analyze data. The in-depth interview was used in order to collect data from 16 domestic tourist who visited main attraction in Bangkok and countryside. The data was collected on Jun 21 - July 1, 2020. As the result from the analysis. It showed that not many people know about virtual tourism and they never try using VR for travel. The preferred destination in Bangkok that informants would like to visit by using VR are nature attraction, adventure attraction, famous temple and museum. Moreover, tourist would like to try virtual tourism to gain a new travel experience and be safe at home during social distancing. Virtual tourism is type of the tourism that provide activity for tourist to enjoy in their free time while staying at home. Therefore, tourism business can still keep contact with their customer. It creates the desire of people to visit the destination after pandemic.